2007
DOI: 10.1152/ajpregu.00068.2007
|View full text |Cite
|
Sign up to set email alerts
|

Preoptic nitric oxide attenuates endotoxic fever in guinea pigs by inhibiting the POA release of norepinephrine

Abstract: Lipopolysaccharide (LPS) administration induces hypothalamic nitric oxide (NO); NO is antipyretic in the preoptic area (POA), but its mechanism of action is uncertain. LPS also stimulates the release of preoptic norepinephrine (NE), which mediates fever onset. Because NE upregulates NO synthases and NO induces cyclooxygenase (COX)-2-dependent PGE2, we investigated whether NO mediates the production of this central fever mediator. Conscious guinea pigs with intra-POA microdialysis probes received LPS intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…The finding that this PGE 2 , however, was not integral to the initiation of the febrile response nor, indeed, to its continuation is novel and intriguing as regards LPS-induced fever, although other fevers caused by certain cytokines have been reported previously to occur independently of central PGE 2 (see Ref. 24). …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The finding that this PGE 2 , however, was not integral to the initiation of the febrile response nor, indeed, to its continuation is novel and intriguing as regards LPS-induced fever, although other fevers caused by certain cytokines have been reported previously to occur independently of central PGE 2 (see Ref. 24). …”
Section: Discussionmentioning
confidence: 86%
“…The free radicals in this case could be generated by the auto-oxidation of NE and/or be nitric oxide; the latter is also released locally in the POA after LPS administration (24). The finding that this PGE 2 , however, was not integral to the initiation of the febrile response nor, indeed, to its continuation is novel and intriguing as regards LPS-induced fever, although other fevers caused by certain cytokines have been reported previously to occur independently of central PGE 2 (see Ref.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that a decrease in central NO increases the SNS activity (48,49). On the other hand, NO could inhibit the release of norepinephrine in the brain (50). Indeed, eNOS gene delivery increased NO production in rostral ventrolateral medulla (rVLM), the cardiovascular center, in cold-exposed rats (47).…”
Section: Nitric Oxide and Cihmentioning
confidence: 99%
“…At the end of the study each rat was sacrificed, the brain removed, frozen on dry ice, and sections of 50μM were cut with a microtome cryostat (Microcom Model HM505E, Waldorf, Germany). Sections were mounted on slides, stained with eosin, air dried and coverslipped, and the location of the needle tip was confirmed (Feleder et al, 2007). Only the data from confirmed placement was considered.…”
Section: Methodsmentioning
confidence: 99%